2011
DOI: 10.1128/aem.05941-11
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Strains Selected on Ciprofloxacin or the Disinfectant Benzalkonium Chloride Exhibit Reduced Susceptibility to Ciprofloxacin, Gentamicin, Benzalkonium Chloride, and Other Toxic Compounds

Abstract: Listeria monocytogenes is a leading agent for severe food-borne illness and death in the United States and other nations. Even though drug resistance has not yet threatened therapeutic interventions for listeriosis, selective pressure associated with exposure to antibiotics and disinfectants may result in reduced susceptibility to these agents. In this study, selection of several L. monocytogenes strains on either ciprofloxacin (2 g/ml) or the quaternary ammonium disinfectant benzalkonium chloride (BC; 10 g/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 35 publications
12
80
0
Order By: Relevance
“…MICs were determined in at least two separate assays, and each strain was assayed in duplicate. To determine efflux pump activity, the inhibitor reserpine (final concentration, 10 mg/liter) was added to each Mueller-Hinton agar plate containing BAC (26,27). All compounds were purchased from Sigma-Aldrich (St. Louis, MO, USA), and stock solutions were prepared and stored according to the manufacturer's recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MICs were determined in at least two separate assays, and each strain was assayed in duplicate. To determine efflux pump activity, the inhibitor reserpine (final concentration, 10 mg/liter) was added to each Mueller-Hinton agar plate containing BAC (26,27). All compounds were purchased from Sigma-Aldrich (St. Louis, MO, USA), and stock solutions were prepared and stored according to the manufacturer's recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…The efflux systems encoded by all of these genes belong to the small multidrug resistance (SMR) pro-tein family (25). Other efflux pumps, such as MdrL (multidrug resistance Listeria) and Lde (Listeria drug efflux) (26,27), which belong to the major facilitator superfamily (MFS) (25), are also associated with L. monocytogenes adaptation and resistance to BAC (26,27).…”
mentioning
confidence: 99%
“…Different studies are suggesting variable incidence of resistance to the Selective pressure has been hypothesized to contribute to the increase in L monocytogenes resistance as BC has been extensively used in food processing and health care environments in the US (124,146,151,190). Furthermore, a number of studies have suggested cross-resistance between BC and antibiotics (182,187,216).…”
Section: Quaternary Ammonium Compound Bezalkonium Chloride (Bc) Thementioning
confidence: 99%
“…Different studies are suggesting variable incidence of resistance to the quaternary ammonium compound bezalkonium chloride ( Selective pressure has been hypothesized to contribute to the increase in L monocytogenes resistance as BC has been extensively used in food processing and health care environments in the US (124,146,151,190). Furthermore, a number of studies have suggested cross-resistance between BC and antibiotics (182,187,216). and L. welshimeri have been found to be more common than L. monocytogenes in food processing environments and in foods, and to grow faster than L. monocytogenes in foods and other media (8,47,104,140,168,197,201,221).…”
Section: Quaternary Ammonium Compound Bezalkonium Chloride (Bc) Thementioning
confidence: 99%
See 1 more Smart Citation